Artes de cordel: linguagem, poética e estética no contemporâneo - Rosilene Alves de Melo (Estudos de Literatura Brasileira Contemporânea)
This article puts into question some issues related to cordel poetics in Brazil,trying to determine how the social insertion of cordel in contemporary times forces on researchers a remodeling of a series of concepts. Highlighting the hybrid character of this poetics, we discuss the artistic and creative nature of cordel while an appropriation of different languages and esthetics.